Individual, family and teacher level correlates of behavioral and cognitive school engagement - Nolvi, Saara (2012)
The aim of the present study was to examine predictors of behavioral school engagement and two cognitive school engagement subdimensions, future aspirations and control and relevance of school work. Another matter of interest was to find out what kind of different school engagement profiles can be identified in terms of engagement, and what are the factors to predict these engagement profiles. The cross-sectional data of the study consisted of Finnish upper comprehensive school students (N=841, 13–16 years) from seven schools located in Middle Finland.